PENGARUH KEGIATAN 3M (MELIPAT, MENGGUNTING, MENEMPEL) TERHADAP KEMAMPUAN MOTORIK HALUS ANAK USIA 5-6 TAHUN DI TK IMMANUEL KIDS MEDAN AMPLAS - Angel Purba, Folin; Elya Siska Anggraini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study .aims to determine the effect of 3M activities (folding, cutting, sticking) on the fine motor skills of 5-6 year old children at Immanuel Kids Kingdergarten, Medan Amplas. This study used a quantitative apporoach with a structured experimental method using a One Group Pretest- Posttest Design, involving a sample of 22 children. Data collection was conducted using a normality test and a t-test to test hypotheses. The children’s scores increased from 10,23 (total score 225) in the pretest to 12,41 (total score 273) in the posttest. Because the calculated t-value was greater then the table t-value, the alternative hypothesis was accepted. Based on these findings, it can be concluded that the 3M activities (folding, cutting, and sticking) have a significant positive effect on improving the fine motor skills of 5-6 year old children at Immanuel Kids Kingdergarten, Medan Amplas.